2021
DOI: 10.1093/mnras/stab1007
|View full text |Cite
|
Sign up to set email alerts
|

The rotation of selected globular clusters and the differential rotation of M3 in multiple populations from the SDSS-IV APOGEE-2 survey

Abstract: In this paper, we analyse 10 globular clusters in order to measure their rotational properties by using high precision radial velocity data from the SDSS-IV APOGEE-2 survey. Out of the 10 clusters we were able to successfully measure the rotation speed and position angle of the rotation axis for 9 clusters (M2, M3, M5, M12, M13, M15, M53, M92, M107). The comparison between our results and previous ones shows a really good agreement within our uncertainties. For four of the globular clusters, M3, M13, M5 and M1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 71 publications
1
8
2
2
Order By: Relevance
“…To verify a direct connection with the formation process it is necessary to check the rotation of the 1P and 2P separately, to identify a differential rotation between the two populations. This has been done for few clusters, however, since the analysed clusters show significantly different behaviours, no firm conclusion has been yet achieved (Milone et al 2018;Cordoni et al 2020a,b;Szigeti et al 2021). Additionally, the strong correlation existing between cluster mass and rotation makes it difficult to disentangle between the relevance of these two properties with respect to the 2P origin.…”
Section: Discussion a N D C O N C L U S I O N Smentioning
confidence: 97%
See 1 more Smart Citation
“…To verify a direct connection with the formation process it is necessary to check the rotation of the 1P and 2P separately, to identify a differential rotation between the two populations. This has been done for few clusters, however, since the analysed clusters show significantly different behaviours, no firm conclusion has been yet achieved (Milone et al 2018;Cordoni et al 2020a,b;Szigeti et al 2021). Additionally, the strong correlation existing between cluster mass and rotation makes it difficult to disentangle between the relevance of these two properties with respect to the 2P origin.…”
Section: Discussion a N D C O N C L U S I O N Smentioning
confidence: 97%
“…Centrally concentrated 2P stars have been indeed observed in a number of clusters (see e.g. Norris & Freeman 1979;Milone et al 2012a;Richer et al 2013;Cordero et al 2014Cordero et al , 2017Bellini et al 2015;Dalessandro et al 2019;Kamann et al 2020;Dondoglio et al 2021;Szigeti et al 2021). The observed differences are milder for more dynamically evolved systems (Dalessandro et al 2019).…”
Section: Introductionmentioning
confidence: 91%
“…We have shown, for the first time, that the young SMC SCs can have internal rotation just after their formation from their natal GMCs. Although this is one key prediction from the present simulation, almost all recent studies of SCs have investigated the internal kinematics of stars in the old Galactic GCs (e.g., Barth et al 2020;Kamann et al 2020;Szigeti et al 2021). Accordingly, it is not possible for the present study to discuss the physical origin of the simulated rotational kinematics of some SCs based on the latest observations of SCs in the SMC.…”
Section: Internal Rotation Of Young Scs In the Smcmentioning
confidence: 84%
“…Recently, Cordero et al (2017) and Kamann et al (2020) analyzed the rotational patterns of two GCs subpopulations and found that extreme SG stars (Na-enhanced and extremely O-depleted) are characterized by a larger rotational amplitude than intermediate SG ones (moderately Na-enhanced and O-depleted). In some cases, instead, no difference as been detected in the rotational patters of distinct populations (Milone et al 2020;Cordoni et al 2020a,b;Szigeti et al 2021). This rotational homogeneity between different populations could hint that these systems are dynamically evolved, where stars are already well kinematically mixed.…”
Section: Introductionmentioning
confidence: 98%
“…The observational study of the kinematics of multiple stellar populations is still in its early stages, but a few investigations have already revealed differences in the rotation amplitudes between stellar populations (Lee 2015(Lee , 2017(Lee , 2018Dalessandro et al 2021;Cordoni et al 2020a;Szigeti et al 2021), with the SG component rotating faster than the FG, with the exception of 𝜔 Cen where Bellini et al (2018) found opposite results. Recently, Cordero et al (2017) and Kamann et al (2020) analyzed the rotational patterns of two GCs subpopulations and found that extreme SG stars (Na-enhanced and extremely O-depleted) are characterized by a larger rotational amplitude than intermediate SG ones (moderately Na-enhanced and O-depleted).…”
Section: Introductionmentioning
confidence: 99%